Induction of seizures and initiation of epileptogenesis by pilocarpine in zebrafish larvae - Gawel, Kinga; Hulas-Stasiak, Monika; Marszalek-Grabska, Marta; Grenda, Anna; Siekierska, Aleksandra; Kosheva, Nataliia; van der Ent, Wietske; Esguerra, Camila V.; Krawczyk, Pawel; Turski, Waldemar A. (Frontiers in Molecular Neuroscience, 2024)
ObjectivePreclinical models of seizures and epilepsy in rodents contributed substantially to the discovery of currently available antiseizure medications. These were also broadly used for investigation of processes of epileptogenesis. Nevertheless, rodent models pose some limitations, thus, new models using alternative species are in high demand. The aim of this study was to describe a new model of seizures/epilepsy induced by the cholinomimetic agent, pilocarpine (PILO), in larval zebrafish.MethodsLocal field potential (LFP) recordings were conducted to analyze electroencephalographic discharges and correlate it with larval behavior. Hematoxylin and eosin (H&E) staining, as well as TUNEL staining were performed to analyze morphology and apoptosis, respectively. Real-time quantitative polymerase chain reaction (qRT-PCR) was undertaken for gene expression analysis.ResultsAcute exposure to PILO, in a concentration-dependent manner, induces electroencephalographic discharges in larval zebrafish, which behaviorally manifest as decreased locomotion and moving time, but enhanced movement velocity. The PILO-induced seizure-like activity is behaviorally distinct from this induced by the application of chemoconvulsant pentylenetetrazole (PTZ). Zebrafish larvae previously exposed to PILO (2 h), after a washing out period, exhibit spontaneous, unprovoked discharges and apoptotic changes in their brains.SignificanceHere, we comprehensively investigated a new model of PILO-induced seizures/epilepsy in larval zebrafish. We propose that this model may be used to study epileptogenesis and for antiseizure drug screening purposes.